Cubosome: A Potential Liquid Crystalline Carrier System - Sharma, Pragya; Dhawan, Surbhi; Nanda, Sanju (Current Pharmaceutical Design, 2020)
Cubosome is a biocompatible, thermodynamically stable and bioadhesive drug carrier that is prepared from certain amphiphilic lipids and surfactants when mixed in a definite ratio. Structurally, they are selfassembled nano-constructed liquid crystalline particles comprising three-dimensionally arranged bicontinuous as well as nonintersecting lipid bilayers that give them a honeycomb-like appearance. Morphological characterization through SAXS (small-angle X-ray scattering) and cryo-TEM (cryo-transmission electron microscopy) revealed that they are square and round shaped particles in the nanometer range. These carriers have two separate aqueous regions and a large interfacial area that allow them to carry a variety of bioactive molecules having hydrophobic, hydrophilic or amphiphilic behavior. One of either two strategies i.e., top-down or bottom-up methods can be adopted to prepare these cubic structures. A number of dispersion techniques like sonication, spray drying, high-pressure homogenization or spontaneous emulsification can be adopted to prepare cubosomes. Their characteristics and benefits like multicompartmental structure, high drug loading, simple and convenient method of preparation, use of biodegradable lipids such as glycerol monooleate, encapsulation of hydrophilic, hydrophobic and amphiphilic moieties, targeted and controlled release make them versatile bioactive carriers that can be administered through multiple biological routes like topical, transdermal, parenteral, and oral. Cubosomes have appreciable applications in various fields especially in the pharmaceutical industry where they are used as potential bioactive carriers. Molecules like paclitaxel, oligonucleotide, δ-amino-levulinic acid, bovine serum albumin, etc. can be easily delivered through this system. This article provides a detailed note on the structure of cubosomes, ingredients and techniques used for their preparation, mechanism of drug release, applications and routes of drug administration, their formulations, patent review and market scenario.
Keywords: monoleins